2015
DOI: 10.1371/journal.pone.0132532
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Susceptibility to Rifampicin and Resistance to Multiple Antimicrobial Agents among Brucella abortus Isolates from Cattle in Brazil

Abstract: This study aimed to determine the susceptibility profile of Brazilian Brucella abortus isolates from cattle to eight antimicrobial agents that are recommended for the treatment of human brucellosis and to correlate the susceptibility patterns with origin, biotype and MLVA16-genotype of the strains. Screening of 147 B. abortus strains showed 100% sensitivity to doxycycline and ofloxacin, one (0.68%) strain resistant to ciprofloxacin, two strains (1.36%) resistant to streptomycin, two strains (1.36%) resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Four isolates of B. melitensis and one isolate of B. abortus showed multidrug resistance against ciprofloxacin, erythromycin, imipenem and rifampicin. These findings are in agreement with the results of Barbosa Pauletti et al who find corresponding resistance among B. abortus isolates from cattle in brazil [62]. All B. melitensis and B. abortus isolates in this study were sensitive to chloramphenicol, gentamicin and tetracycline.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Four isolates of B. melitensis and one isolate of B. abortus showed multidrug resistance against ciprofloxacin, erythromycin, imipenem and rifampicin. These findings are in agreement with the results of Barbosa Pauletti et al who find corresponding resistance among B. abortus isolates from cattle in brazil [62]. All B. melitensis and B. abortus isolates in this study were sensitive to chloramphenicol, gentamicin and tetracycline.…”
Section: Discussionsupporting
confidence: 94%
“…The phenotypic antimicrobial resistance against ciprofloxacin (25%), erythromycin (87.5%), imipenem (25%) and rifampicin (37.5%) of B. abortus isolated in this study was not proved previously. Multidrug resistant strains of B. abortus isolated from cattle in this study were reported previously in Brazil [62]. Four isolates of B. melitensis and one isolate of B. abortus showed multidrug resistance against ciprofloxacin, erythromycin, imipenem and rifampicin.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Another study of 27 isolates of Brucella species including Brucella abortus and Brucella Canis in Brazil showed decreased susceptibility to RIF and SXT in 10 and 5 isolates, respectively (24). In addition, a study of 147 B. abortus strains from cattle in Brazil reported reduced susceptibility to RIF in 36% and resistance to RIF in 2% of isolates (25). Reports of such a high prevalence of reduced sensitivity among Brucella isolates from livestock could be a warning alarm for the increasing incidence of RIF-resistant brucellosis in the community.…”
Section: Discussionmentioning
confidence: 98%
“…It was discussed earlier that in regions with prevalent brucellosis there is a potential of developing of MDR-TB because of a treatment of both diseases with the same frontline antibiotics [ 26 ]. In reality, the provinces of Kazakhstan with high rates of MDR-TB also have high rates of Brucella resistance to rifampricin [ 27 29 ]. Among other countries of the world only Kyrgyzstan (which borders Kazakhstan) also has the high rates of both MDR-TB and brucellosis.…”
Section: Discussionmentioning
confidence: 99%